Eye as the First Clue: Behçet’s Disease Unveiled by Retinal Vasculitis and Vein Occlusion - Gull, Ambreen; Sajjad, Arsalan; Rasool, Wajeeha; Niazi, Fuad Ahmad Khan (Journal of Rawalpindi Medical College, 2026)
Behçet's disease is a multisystem vasculitis of unknown etiology that is chronic and recurrent. One of the most severe and vision-threatening implications is ocular inflammation. We present a case of severe ocular Behçet's disease with occlusive retinal vasculitis in a young male. A 20-year-old boy had gradually deteriorating vision in both eyes for three months before experiencing a sudden loss of vision in the left eye for two weeks. Ocular examination showed bilateral anterior uveitis with vitritis and perivasculitis. Branch retinal vein occlusion (BRVO) with macular edema and macular pseudohole was seen in the left eye, which was confirmed by fundus fluorescein angiography and optical coherence tomography. A positive pathergy test, as well as repeated oral and vaginal ulcers, confirmed the diagnosis of Behçet's syndrome with panuveitis and occlusive vasculitis. Adalimumab, azathioprine, and systemic corticosteroids were used to treat the patient; this led to a partial recovery of vision and a noticeable reduction in inflammation. Early detection of Behçet's uveitis and timely beginning of immunomodulatory therapy are essential to prevent irreversible retinal damage and subsequent visual loss. Keywords: Behçet’s Disease, Retinal Vasculitis, Branch Retinal Vein Occlusion, Macular Edema, Adalimumab, Uveitis